CROSSING INDONESIA'S STARTUP ECOSYSTEM UNVEILING INNOVATION AND RESILIENCE IN THE CREATIVE ECONOMY LANDSCAPE - Rudy Parlindungan Siahaan; Ahmad Rizani; Henny Noviany; Lina Affifatusholihah; Rahma Helal Al_ Jbour (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
This study thoroughly examines Indonesia's burgeoning startup ecosystem, focusing on the symbiotic relationship between technological advancements, innovative dynamics, and entrepreneurial resilience within the creative economy. Employing a meticulous mixed-methods approach, the research dissects the intricate interplay of these elements, providing nuanced insights into the nation's entrepreneurial landscape. From the impressive annual growth rate of 20% to the disruptive models commanding a substantial 30% market share, the study delves into the transformative role of startups. The research illuminates the multifaceted nature of Indonesia's startup ecosystem by scrutinizing the technological evolution with a 35% Market Disruption Index and the sectoral diversity reflected in a 45% Adaptive Nature Index. It underscores the pivotal influence of government initiatives, with a discernible 50% impact on startup growth, and emphasizes the entrepreneurial resilience showcased through a commendable 55% regulatory compliance rate. The study concludes with a focus on the critical importance of a robust investment climate, reflected in a notable 60% funding success rate, shaping the trajectory of Indonesia's entrepreneurial endeavors. This research contributes to a deeper understanding of the dynamic interplay between technology and entrepreneurship, offering valuable insights for policymakers, entrepreneurs, and scholars.